Prosthetic Rehabilitation with Artificial Palpebra of an Ocular Defect with Contracted Socket - Sri Budi Barunawati; Intan Ruspita; Endang Wahyuningtyas; Chrisdina Puspita Sari (Indonesia Prosthodontic Association, 2024)
Eyes are one of the most important organs of the body which are set inside the protective orbital bone. Loss of an eye can be caused by congenital defects, trauma, or tumors. The removal of the eyeball (enucleation) may cause a massive impact on the self-image, confidence, and personality of an individual. Acceptable cosmetic results usually can be obtained with an ocular prosthesis which is an artificial maxillofacial prosthesis to replace the lost eye. This paper describes the prosthetic rehabilitation of a 71-year-old male patient with a left ocular defect accompanied by a contracted socket caused by the poorly fitting old prosthesis which results in subpar cosmesis. The soft tissue around the eye is normal, but the palpebral conjunctiva forms an abnormal adhesion to the eye socket. An impression was made using a custom tray and alginate in the defect area, followed by filling the impression with gypsum type 3 to get a working model, from which a wax model was made and adjusted to the patient. Sclera and ocular acrylic prostheses were made on the basis of an adjusted wax model. The prosthesis was then polished and colored according to the contralateral eye, followed by the manufacturing of an artificial palpebra made of silicone for a more aesthetic result. The custom-made eye prosthesis with silicone palpebra is an artistic solution for the treatment of ocular defects with contracted sockets. This technique was able to improve the patient’s psychological and emotional status.